2013
DOI: 10.1523/jneurosci.1013-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Differential Contribution of Hippocampal Circuits to Appetitive and Consummatory Behaviors during Operant Conditioning of Behaving Mice

Abstract: Operant conditioning is a type of associative learning involving different and complex sensorimotor and cognitive processes. Because the hippocampus has been related to some motor and cognitive functions involved in this type of learning (such as object recognition, spatial orientation, and associative learning tasks), we decided to study in behaving mice the putative changes in strength taking place at the hippocampal CA3-CA1 synapses during the acquisition and performance of an operant conditioning task. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 53 publications
(21 reference statements)
5
59
0
Order By: Relevance
“…In contrast, it has been recently shown that the hippocampus is not very much involved in the entire process of the acquisition of instrumental learning tasks (Jurado-Parras, Jurado-Parras et al, 2013), although the CA3-CA1 is modulated in strength by the performance of specific appetitive (e.g., pressing a lever in order to obtain a piece of food) vs. consummatory (e.g., eating the collected pellet) behaviors . This involvement of the hippocampus in specific behaviors related to operant conditioning tasks is extensible to appetitive reinforcements (pressing a lever to obtain an electrical stimulation of a positive reinforcing center, such as the medial septum) vs. internal ones (in order to receive the self-stimulation) (Vega-Flores, Rubio, Jurado-Parras, Gómez-Climent, Hampe, Manto, Soriano, Pascual, Gruart, & Delgado-García, 2014).…”
Section: The Hippocampal Ca3-ca1 Synapse Is Modified During the Acquimentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, it has been recently shown that the hippocampus is not very much involved in the entire process of the acquisition of instrumental learning tasks (Jurado-Parras, Jurado-Parras et al, 2013), although the CA3-CA1 is modulated in strength by the performance of specific appetitive (e.g., pressing a lever in order to obtain a piece of food) vs. consummatory (e.g., eating the collected pellet) behaviors . This involvement of the hippocampus in specific behaviors related to operant conditioning tasks is extensible to appetitive reinforcements (pressing a lever to obtain an electrical stimulation of a positive reinforcing center, such as the medial septum) vs. internal ones (in order to receive the self-stimulation) (Vega-Flores, Rubio, Jurado-Parras, Gómez-Climent, Hampe, Manto, Soriano, Pascual, Gruart, & Delgado-García, 2014).…”
Section: The Hippocampal Ca3-ca1 Synapse Is Modified During the Acquimentioning
confidence: 96%
“…Particular attention will be paid to the contribution of specific hippocampal, prefrontal, and other cortical and subcortical circuits to the acquisition to the two main types of associative learning, represented by the classical conditioning of eyelid responses, and selective operant conditioning tasks (CarreteroGuillén et al, in press;Eleore, López-Ramos, Yi, & DelgadoGarcía, 2007;Gruart et al, in press;Jurado-Parras, Sánchez-Campusano, Castellanos, del-Pozo, Gruart, Delgado-García, 2013;Leal-Campanario, Delgado-García, & Gruart, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the hippocampus has been implicated in resolving approach-avoidance discrepancies in situations in which two opposing response tendencies are experienced simultaneously [15, 16]. Other findings suggest adaptive response selection is based on the contribution of the hippocampus to the context-dependent inhibition of approach tendencies [14, 17, 18]. The retrieval of situationally-appropriate memories by contextual cues and the reduction of interference by memories formed in other contexts are also considered functions of the hippocampus [19, 20].…”
Section: The Modelmentioning
confidence: 99%
“…Changes in synaptic weights during the acquisition of classical24 and instrumental34 conditioning paradigms have been reported for the above-mentioned neural centers, as well as during the performance of inhibitory avoidance learning39 and object recognition4041 tasks. In addition, brain state can change rapidly such as in the case of attention, and transiently modulate neural responsiveness4243444546.…”
mentioning
confidence: 95%
“…Within the hippocampus, the CA1 region has been related to appetitive and consummatory behaviors during operant conditioning tasks34, as well as during novelty detection3536. The SUB is a hippocampal output structure receiving synaptic excitation from CA1 pyramidal cells, and represents an important connecting node for processing spatial information and body movements.…”
mentioning
confidence: 99%